What is money? - Smithin, John N. (Routledge international studies in money and banking ;, 2000)
This volume provocatively rethinks the economics, politics and sociology of money and examines the classic question of what is money. Starting from the two dominant views of money, as neutral instrument and as social relation, What is Money? presents a thematic, interdisciplinary approach which points to a definitive statement on money. Bringing together a variety of neclassical and heterodox perspectives, this work collects the latest thinking of some of the best-known economics scholars on the question of money. The contributors are Victoria Chick, Kevin Dowd, Gilles Dostaler,